PENINGKATAN FUNGSI JALUR TROTOAR PADA KAWASAN PENDIDIKAN UNTUK MEMFASILITASI KEBUTUHAN SARANA PEJALAN KAKI - Norman Kartaatmadja; Zenal Mutaqin (Jurnal Tekno Global, 2022)
The need for pedestrian fasilities in the area of Jalan Balayudha Palembang Muhammadiyah School is very important to be fasilitated, considering the intensity of the number of pedestrian is dominated by some students from various levels,including the surrounding community to work by utilizing the raad as a means of pedestrian. The current condition of pedestrian facilities is not technically adequate, besides that the shoulder of the road is used for selling and parking vehicles. To improve service, safety and comfort for pedestrians in the Muhammadiyah School areaÂ  in order to improve the function oh the sidewalk as a pedestrian facility. Therefore, it is necessary to conduct research where the community is expected to assess the condition of the pedestrian path. That the impact of the assessment can be used as a basis for planning in the provision of adequate pedestrian facilities. The purpose of the study was to determine the level of influence of respondents as road users on the condition of pedestrian facilities and to facilities the need for pedestrian facilities through pedestrian planning. This research method uses a quantitative approach by developing data from the field through interviews and questionnaires. The analysis process uses regression which aims to measure the effect of the independen variabel on the dependent variable. Based on the results of the analysis, it shows that the factor of physical quality, feasibility, security, comfort, regualations and environmental knowledge have a very strong role to facilitate the need for pedestrian facilities through the pedestrian development plan at the Muhammadiyah Balayuda School Palembang with an influence level of 0.92 percent (92%).